Asymmetric Labor Markets, Southern Wages, and the Location of Firms - Alireza Naghavi (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper studies the behavior of firms towards weak labor rights in developing countries (South). A less than perfectly elastic labor supply in the South gives firms oligopsonistic power tempting them to strategically reduce output to cut wages. In an open economy, competitors operating in perfectly competitive labor markets meanwhile enjoy less aggressive competitors and raise output. Finally, competition effect reduces the ex-post output of a relocating firm. These effects reduce relative profitability of the South casting doubts on traditional beliefs that multinationals are attracted to regions with lower wages. Adopting a minimum wage unambiguously enhances Southern competitiveness and welfare.
Keywords: J80; F23; J42; F12; R38; L13; 330; Labor standards; Labor market imperfection; Oligopsony; Location of firms; Minimum wages; Strategic behavior; Multinationals; Southern welfare